Assessment of Elkhorn Coral Populations and Associated Herbivores in Akumal, Mexico - Mudge, Laura; Alves, Catherine; Figueroa-Zavala, Baruch; Bruno, John (Frontiers in Marine Science, 2019)
Coral decline in the Caribbean is marked by the loss of habitat-forming corals, such as elkhorn coral (Acropora palmata). Elkhorn coral recovery has been isolated and patchy, but recently a “re-sheeting” phenomenon, in which elkhorn tissue grows over standing dead coral skeletons, was observed along the reefs in the Mexican Yucatán peninsula. Little is known about the ecological factors contributing to “re-sheeting”, but it is hypothesized that grazing from herbivores provides top-down control of algal growth and promotes coral recovery. The purpose of this study was to evaluate the status of elkhorn populations in Akumal, Mexico and determine if Diadema urchins or parrotfish populations are associated with higher elkhorn abundance and lower algal cover. To achieve this objective, we surveyed 12 spur and groove reef sites in Akumal, where re-sheeting was recently observed, and measured elkhorn coral and herbivore population metrics. We found that both herbivore groups are associated with increasing elkhorn coral presence and cover, and lower macroalgal cover. Additionally, we tested for sampling bias in counting Diadema urchins and found that a significant difference in urchins counts between paired day and night transects on shallow, high complexity reefs Our results suggest that historically important herbivore groups may be contributing to the recovery of elkhorn coral in Akumal by facilitating tissue re-sheeting.